Generation Z and key-factors on e-commerce: A study on the Portuguese tourism sector - Jorge Vieira; Rui Frade; Raquel Ascenso; Inês Prates; Filipa Martinho (Administrative Sciences, 2020)
In recent years, tourism has experienced remarkable growth worldwide. This sector is rapidly becoming the main export activity and the most important source of GDP growth in several countries. In Portugal, it represented around 19.7% of exports in 2019. The internet and online platforms contributed decisively to this growth. Generation Z already represents a considerable portion of society and, in the coming years, will become the central consumer segment. With this research, we intend to identify the key factors in the decision to purchase online, in Generation Z individuals, in the Portuguese tourism sector. We carried out a characterization of the sector, a bibliographic review and the identification of key variables. We applied a structured questionnaire to a sample of 233 individuals aged between 10 and 25 years. Subsequently, the data were processed using descriptive methodologies and association tests between variables. The key factors in the decision to purchase tourism products/services in Generation Z are Trust, Price, the use of aggregating websites, WOM/EWOM, the Offer of products/services online and the Online experience. In the opposite direction, it was given less importance to Convenience, Reviews on tourism websites, Tourism Advertising, Social networking and the possibility of Canceling the reservation. This study allows us to establish the bases for future research, to help researchers to understand Generation Z consumption habits.
Keywords: 350; generation Z; e-commerce; tourism